1979
DOI: 10.2134/agronj1979.00021962007100030020x
|View full text |Cite
|
Sign up to set email alerts
|

N Deprivation in Maize During Grain‐Filling. I. Accumulation of Dry Matter, Nitrate‐N, and Sulfate‐S1

Abstract: Maize (Zea mays L.) has a noted propensity for accumulating large amounts of nitrate‐N (NO3‐N). However, the availability of such NO3‐N for assimilation during periods of restricted N supply has not been assessed. In addition, the availability of sulfate‐S (SO4‐S) affects the accumulation and assimilation of NO3‐N. Little is known about the effect of NO3‐N supply on SO4‐S accumulation. Such information is vital to efforts to improve the efficiency of nutrient utilization by crops. The objective of this greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0
3

Year Published

1981
1981
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 5 publications
2
4
0
3
Order By: Relevance
“…3). These findings are consistent with the reports of Friedrich et al (1979) and Wilhelm et al (2005), who found that nitrate concentrations tended to decrease with increasing height in corn plants and is consistent with the knowledge that nutrient translocation after physiological maturity goes from top to bottom within each individual plant. The slopes of the linear regressions shown in Figure 3 indicate that the relative concentrations of nitrate in the upper third of the normal samples tended to be about 55% of those found in the lower third.…”
Section: Distribution Of Nitrate In the Cornstalksupporting
confidence: 93%
“…3). These findings are consistent with the reports of Friedrich et al (1979) and Wilhelm et al (2005), who found that nitrate concentrations tended to decrease with increasing height in corn plants and is consistent with the knowledge that nutrient translocation after physiological maturity goes from top to bottom within each individual plant. The slopes of the linear regressions shown in Figure 3 indicate that the relative concentrations of nitrate in the upper third of the normal samples tended to be about 55% of those found in the lower third.…”
Section: Distribution Of Nitrate In the Cornstalksupporting
confidence: 93%
“…C ORN takes up 60 to 75% of its total N after the onset of the reproductive stage, tasseling (Friedrich et al, 1979;Mills and McElhannon, 1982). Therefore, the availability of N from tasseling through maturity can affect the plant's vegetative growth and ear development.…”
mentioning
confidence: 99%
“…Volgens Warnke & Barber (1973) is die optimum verhouding 1: 1. Hierdie navorsers het die droemassas egter op vroee groeistadiums gemeet en volgens Schrader (1978) en Friedrick, Schrader & Nordheim (1979) is maksimum nitraatopname eers 63 dae na plant. Die bepaling van die optimum nitraat:ammoniumverhouding moet daarom tot volwassenheid gedoen word.…”
Section: • Aan Wie Korrespondensie Gerig Moet Wordunclassified